Finding solutions to Asia?s water challenges through integrated water-resources management - Vermillion, Douglas L. (2003)
Paper for the Ministerial Roundtable Dialogue on Water Sector Challenges, Policies and Institutional Development in Asia, United Nations Conference Center, Bangkok, United Nations Conference Center, Bangkok, 22-23 May 2002